2013
DOI: 10.1017/s0033291713000160
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive trio: relationship with major depression and clinical predictors in Han Chinese women

Abstract: BackgroundPrevious studies support Beck's cognitive model of vulnerability to depression. However, the relationship between his cognitive triad and other clinical features and risk factors among those with major depression (MD) has rarely been systematically studied.MethodThe three key cognitive symptoms of worthlessness, hopelessness and helplessness were assessed during their lifetime worst episode in 1970 Han Chinese women with recurrent MD. Diagnostic and other risk factor information was assessed at perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
8
1
Order By: Relevance
“…Beck postulated a negative view of the world, of the self, and of the future as the hallmark symptoms of depression, and suggested they were more than mere symptoms – that they caused depression. We agree with this perspective, particularly in the light of the empirical evidence supporting it (e.g., Abela & D'Alessandro, ; Alloy et al ., ; Hankin, Abramson, Miller, & Haeffel, ; Wang et al ., ) – and we further suggest that the negative view of the future is the first among equals in the triad. Much research and therapeutic work focuses on negative views of the self (e.g., Fennell, ; Metalsky, Joiner, Hardin, & Abramson, ; Orth, Robins, & Roberts, ), but negative views of the future may matter even more; we hypothesize that the entire cognitive triad may actually boil down to negative future‐thinking.…”
Section: Mental Representation Of Possible Futuresmentioning
confidence: 50%
“…Beck postulated a negative view of the world, of the self, and of the future as the hallmark symptoms of depression, and suggested they were more than mere symptoms – that they caused depression. We agree with this perspective, particularly in the light of the empirical evidence supporting it (e.g., Abela & D'Alessandro, ; Alloy et al ., ; Hankin, Abramson, Miller, & Haeffel, ; Wang et al ., ) – and we further suggest that the negative view of the future is the first among equals in the triad. Much research and therapeutic work focuses on negative views of the self (e.g., Fennell, ; Metalsky, Joiner, Hardin, & Abramson, ; Orth, Robins, & Roberts, ), but negative views of the future may matter even more; we hypothesize that the entire cognitive triad may actually boil down to negative future‐thinking.…”
Section: Mental Representation Of Possible Futuresmentioning
confidence: 50%
“…The analysis was performed on three sets of items: (i) the nine DSM-IV criteria for MD; (ii) 14 items representing the disaggregated DSM-IV criteria (i.e. increased and decreased appetite and weight, insomnia or hypersomnia, and psychomotor agitation or retardation); and (iii) 27 items consisting of detailed assessments of DSM-IV criteria and symptoms of melancholia, anxiety and Beck’s cognitive trio (Beck & Alford, 2008; Wang et al 2013). We then attempted to validate the identified classes by examining other depression-related clinical features, co-morbidities and environmental risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Alas, some studies have shown that a lack of parental warmth and care and parental control of children with negative psychology such as criticism and guilt induction are related to patients' depression and negative cognitive style (49). And parental overprotection in childhood may as well increase the risk of cognitive impairment, and neurocognitive impairment may be a risk factor for SRB (50,51). Therefore, to mitigate the risk of SRB, adjusting the appropriate rearing style and improving the communication between parents and children were suggested.…”
Section: Discussionmentioning
confidence: 99%